Evaluation of Accounting Learning Models: Implementation of Context, Input, Process, and Product (CIPP) Evaluation on Problem-Based Learning Models - Basuki Basuki; Nurul Anriani (research, training and philanthropy institution Natural Aceh, 2023)
Accounting is one of the fields of science that needs more to learn from the theoretical side alone, but it will be easier to understand with real bookkeeping practice. Developing accounting teaching materials is one of the efforts to improve student competence. The learning model with problem base learning is used by lecturers of accounting courses at the University of Muhammadiyah Tangerang. This study aims to evaluate how accounting learning with the PBL model. This type of research is evaluation research that uses a qualitative descriptive methodology and a CIPP assessment model. The results showed that learning Accounting courses using PBL by updating teaching materials, making teaching materials easily accessible to students. The downside of problem-based learning (PBL) is that not all accounting materials can be applied to this model. PBL teaching can increase student engagement in classroom exercises